Simulation of boundary layer characteristics using 1-D PBL model over Goa during ARMEX-I - DAS, Yashvant; MOHANTY, Uma Charan (Contributions to Geophysics and Geodesy, 2021)
This paper presents the characteristic features involved in the variability of the planetary boundary layer (PBL) over Goa (15.38°N, 73.83°E), located in the west coastal belt of Indian Peninsula. This work was carried out during the Arabian Sea Monsoon Experiment (ARMEX) field campaign, which was the second observational programme under the Indian Climate Research Program (ICRP), during June-August 2002. A high-resolution sounding data comprising the vertical profiles of temperature, humidity, zonal and meridional component of wind, along the vertical, was obtained during ARMEX-I observational campaign that was used to study the PBL characteristics over Goa during convectively active and convectively suppressed episodes in June and July 2002, respectively. For this purpose a one-dimensional multi-level PBL model with a TKE-ε closure scheme was used. The temporal evolution of turbulent kinetic energy (TKE), planetary boundary layer (PBL) height, sensible and latent heat fluxes are simulated for these specific convective episodes during ARMEX-I. The model also generates the vertical profiles of potential temperature, specific humidity, zonal and meridional wind that compare reasonably well with the observations.